Persistência da infecção por Leishmania braziliensis em camundongos BALB/c mediada por citocinas e quimiocinas - Viana, Sayonara de Melo (2013)
Leishmania braziliensis is the main causative agent of American cutaneous leishmaniasis in Brazil. Altough L. braziliensis infection is self-limited it is distinguished by its latency and chronicity and can persist in mice and patients even after spontaneous clinical cure or treatment. Little is known about the persistence feature in L. braziliensis’ infection in humans and mice. Thereby, the aim of this study was to characterize the parasite’s persistence in the murine model. The parasite load, lesion thickness and pattern of cytokines and chemokines involved in persistence were evaluated through BALB/c mice infection with a L. braziliensis strain and observation for 90 days after infection. The results showed that parasites gradually disappear in the footpad, while the parasite load was sustained in the draining lymph node until 90 days post-infection (p.i). In the footpad, TNF-α expression was higher at 30 days p.i, followed by the decrease in parasite load and lesion thickness in the site. IL-10 and TGF-β were more expressed at first and decreased after 30 days of infection. A higher concentration of TNF-α and IFN-γ was observed at 15 and 30 days post-infection in the draining lymph node, while IL-4 was significantly increased at 15 days post-infection, and IL-10 and TGF-β were the predominant cytokines after 90 days of infection. CCL2, CCL3, CXCL1 e CXCL10 were expressed in the footpad, with a peak at 30 days p.i. and reduction at 60 days. In the draining lymph node, CCL2 and CXCL10 presented a low expression at first, increasing to a peak at 45 days p.i., while CCL3 was more expressed at 30 days p.i., the same period of the maximum lesion thickness. In our work, we observed that Leishmania persists in draining lymph nodes, while CCL2, CXCL10, IL-10 and TGF- are significantly expressed/produced. These results indicate that these citokynes act synergistically, which can determinate parasite persistence in the draining lymph node.